Mitral Valve Subacute Endocarditis Caused by Abiotrophia Defectiva: A Case Report - Catarina Faria; Renato Guerreiro; Sofia Cruz; Marco Fernandes (Clinics and Practice, 2021)
Abiotrophia defectiva is a rare agent of endocarditis and subacute presentation may delay the diagnosis. We present the case of a 41-year-old male who was admitted to the hospital for further investigation regarding a consumptive syndrome with microcytic anaemia. Past medical history included new-onset mitral insufficiency followed by an ischaemic stroke due to small vessel disease. Thoraco-abdominal computed tomography revealed a splenic infarction. In the presence of two ischaemic events associated with mitral valve disease of unknown aetiology, we considered the possibility of subacute endocarditis. Blood cultures were positive for Abiotrophia defectiva, and transoesophageal echocardiography confirmed the diagnosis. As a subacute presentation of endocarditis, the paucity of symptoms caused a five-month delay in diagnosis. New-onset valvular disease and a stroke in an otherwise healthy young patient should always prompt proper investigation. This case highlights several complications caused by septic emboli of undiagnosed and untreated endocarditis.